Anti-Inflammatory Effect of Emblica officinalis in Rodent Models of Acute and Chronic Inflammation: Involvement of Possible Mechanisms. (21st August 2014) - Golechha, Mahaveer; Sarangal, Vikas; Ojha, Shreesh; Bhatia, Jagriti; Arya, Dharmveer S.
Abstract : Emblica officinalis, commonly known as amla in Ayurveda, is unarguably the most important medicinal plant for prevention and treatment of various ailments. The present study investigated the anti-inflammatory activity of hydroalcoholic extract of Emblica officinalis (HAEEO). Acute inflammation in rats was induced by the subplantar injection of carrageenan, histamine, serotonin, and prostaglandin E2 and chronic inflammation was induced by the cotton pellet granuloma. Intraperitoneal (i.p.) administration of HAEEO at all the tested doses (300, 500, and 700 mg/kg) significantly( P < 0.001 ) inhibited rat paw edema against all phlogistic agents and also reduced granuloma formation. However, at the dose of 700 mg/kg, HAEEO exhibited maximum anti-inflammatory activity in all experimental models, and the effects were comparable to that of the standard anti-inflammatory drugs. Additionally, in paw tissue the antioxidant activity of HAEEO was also measured and it was found that HAEEO significantly( P < 0.001 ) increased glutathione, superoxide dismutase, and catalase activity and subsequently reduced lipid peroxidation evidenced by reduced malondialdehyde. Taken all together, the results indicated that HAEEO possessed potent anti-inflammatory activity and it may hold therapeutic promise in the management of acute and chronic inflammatory conditions.